EFFECT OF ADDITION FROM EGG YOLK OF DIFFERENT AVIAN TO TRIS EXTENDER ON FREEZING SEMEN TRAITS OF AWASSI RAMS - & et al., Saieed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The objective of this study was to investiget the effect of different kinds of egg yolk (hen, quail, turkey, and duck) on the awassi ram semen quality after cryopreservation. The semen was collected by using artificial vagina from four awassi rams and then evaluated , after pooling the semen samples and dilution with tris which contain egg yolk made from poultry birds (10%) and glycerol (5%).The samples were kept in 4C for two hours and then exposed to liquid nitrogen vapor for (10min) and suck in liquid nitrogen, one month later, the samples were thawed at 37C for(5min).the sperm motility, membrane integrity, the percentage of dead and abnormal sperm and DNA fragmentation determination were evaluated. The results showed that yolk of quail egg recorded the higher percent of sperm motility and membrane integrity in comparison with other birds (40.85, 43.85%) respectively. No significant (P>0.05) differences were recorded between quail yolk egg and duck yolk egg for dead and abnormal sperm. The yolk of quail eggs Foard the lowest percentage of DNA fragmentation (8.8%) while no significant difference was recorded between yolk of hen egg, turkey and duck. It can be conclude that the ability of using yolk of quail eggs as substitute of yolk of hen in the semen ram dilutions.